(untitled) (Research, Society and Development, 2022)
Polycystic ovary syndrome (PCOS) is a very common disease affecting about 5% to 10% of the female population and being one of the main causes of infertility in women of reproductive age. It is characterized by hormonal disorders such as menstrual irregularity or amenorrhea, which can result in anovulation, hirsutism, acne, alopecia and obesity. The present research aimed to find out how prevention and quality of life can benefit these women with PCOS. This was a narrative review of the literature, carried out in the PUBMED, BIREME and SCIELO databases, with the descriptors “Polycystic ovarian syndrome/Polycystic ovarian syndrome”, “Polycystic ovary/polycystic ovarian syndrome”, “Nutritional treatment of PCOS / nutritional treatment of POS", “Metformin/ Metformin” and “Anticonceptional/ Contraceptive”. The results showed that lifestyle changes, physical activity and vitamin and mineral supplement intake have a positive effect on the health of women with PCOS. Thus, nutritional aspects tend to be paramount, as it helps to maintain food diversification balanced in the needs of each patient with this syndrome, and weight reduction of 5 to 10% can improve several symptoms in PCOS.